Community-University Partnership Characteristics for Translation: Evidence From CDC's Prevention Research Centers - Young, Belinda-Rose; Leeks, Kimberly D.; Bish, Connie L.; Mihas, Paul; Marcelin, Rose A.; Kline, Jennifer; Ulin, Brigette F. (Frontiers in Public Health, 2020)
Background: The Centers for Disease Control and Prevention's Prevention Research Centers (PRC) Program supports community engagement and partnerships to translate health evidence into practice. Translation is dependent on the quality of partnerships. However, questions remain about the necessary characteristics to develop and maintain translation partnerships. Aim: To identify the characteristics that influence community-university partnerships and examine alignment with the Knowledge to Action (K2A) Framework. Methods: Final Progress Reports (N = 37) from PRCs funded from September 2009 to September 2014 were reviewed in 2016–2017 to determine eligibility. Eligible PRCs included those that translated an innovation following the applied research phase (2009–2014) of the PRC award (n = 12). The PRCs and the adopters (i.e., community organizations) were recruited and participated in qualitative interviews in 2017. Results: Ten PRCs (83.3% response rate) and four adopters participated. Twelve codes (i.e., elements) were found that impacted partnerships along the translation continuum (e.g., adequate communication, technical assistance). Each element aligned with the K2A Framework at multiple steps within the translation phase. The intersection between the element and step in the translation phase is termed a “characteristic.” Using interview data, fifty-two unique partnership characteristics for translation were found. Discussion and Conclusion: The results suggest multiple characteristics that impact translation partnerships. The inclusion of these partnership characteristics in policies and practices that seek to move practice-based or research-based evidence into widespread use may impact the receptivity by partners and evidence uptake by communities. Using the K2A Framework to assess translation partnerships was helpful and could be considered in process evaluations to inform translation partnership improvement.